"Información sobre métodos anticonceptivos y riesgo de embarazo en estudiantes de Enfermería. Sede Valle Jequetepeque. Universidad Nacional de Trujillo. 2010" - Diaz Esteves, Rosa Angela (2010)
This research study is a descriptive, correlational was conducted with students in the School of Nursing, National University of Trujillo - See Jequetepeque Valley during the months of January to August 2010 with the aim of determine the relationship between the level of information about contraception and pregnancy risk nursing students. The sample universe consisted of 115 students selected based on inclusion criteria. The data collection was obtained by applying two-denominated instruments: Survey of Level of information about contraceptive methods, and Level Rating Scale Risk Pregnancy. The data were tabulated and presented in tables and statistical graphs single and double entry. The analysis of the relationship between the study variables was performed by applying two tests, the test of independence of criteria or Chi square and Student t lest. After the analysis reached the following conclusions: The 60.9 percent of students in study had a level of information about contraception regularly followed by a level 31.3 per cent poor, and only 7.8 percent with good level. The 49.6 percent of students showed no risk of pregnancy followed by a 47 percent lower risk of pregnancy and 3.5 percent of high risk. Highly significant relationship exists between the level of information about contraception and pregnancy risk students.